Overweight and obesity among young women in Poland - the problem of infertility and prenatal complications - Anna Fabian-Danielewska; Katarzyna Korabiusz; Agnieszka Malita; Monika Stecko; Agata Wawryków; Inga Janik; Martyna Maciejewska; Mirela Niedzielska; Agnieszka Wilczyńska (Journal of Education, Health and Sport, 2018)
Overweight and obesity in young population is currently one of a highest importance problems in family practice. Among the examined young women in local community BMI over 25 kg/m2, defined as overweight, concerned 34 patients, which is 25% of the examined group, and obesity (BMI over 30 kg/m2) concerned 10 women, which is 7% of the study group. The influence of the woman's excessive body weight affects the pregnancy at every stage of reproduction. Obesity causes problems with pregnancy, numerous complications of pregnancy, hinders childbirth and postpartum period.